Reconstituting NK Cells After Allogeneic Stem Cell Transplantation Show Impaired Response to the Fungal Pathogen Aspergillus fumigatus - Weiss, Esther; Schlegel, Jan; Terpitz, Ulrich; Weber, Michael; Linde, Jörg; Schmitt, Anna-Lena; Hünniger, Kerstin; Marischen, Lothar; Gamon, Florian; Bauer, Joachim; Löffler, Claudia; Kurzai, Oliver; et al. (Frontiers in Immunology, 2020)
Delayed natural killer (NK) cell reconstitution after allogeneic stem cell transplantation (alloSCT) is associated with a higher risk of developing invasive aspergillosis. The interaction of NK cells with the human pathogen Aspergillus (A.) fumigatus is mediated by the fungal recognition receptor CD56, which is relocated to the fungal interface after contact. Blocking of CD56 signaling inhibits the fungal mediated chemokine secretion of MIP-1α, MIP-1β, and RANTES and reduces cell activation, concluding a functional role of CD56 in fungal recognition. We collected peripheral blood of recipients of an allograft on defined time points after alloSCT (day 60, 90, 120, 180). NK cells were isolated, directly challenged with live A. fumigatus germ tubes, and cell function was analyzed and compared to healthy individuals. After alloSCT, NK cells displayed a higher percentage of CD56brightCD16dim cells throughout the time of blood collection. However, CD56 binding and relocalization to the fungal contact side were decreased. We could correlate this deficiency to the administration of corticosteroid therapy that further negatively influenced the secretion of MIP-1α, MIP-1β, and RANTES. As a consequence, the treatment of healthy NK cells ex vivo with corticosteroids abrogated chemokine secretion measured by multiplex immunoassay. Furthermore, we analyzed NK cells regarding their actin cytoskeleton by Structured Illumination Microscopy (SIM) and flow cytometry and demonstrate an actin dysfunction of NK cells shown by reduced F-actin content after fungal co-cultivation early after alloSCT. This dysfunction remains until 180 days post-alloSCT, concluding that further actin-dependent cellular processes may be negatively influenced after alloSCT. To investigate the molecular pathomechansism, we compared CD56 receptor mobility on the plasma membrane of healthy and alloSCT primary NK cells by single-molecule tracking. The results were very robust and reproducible between tested conditions which point to a different molecular mechanism and emphasize the importance of proper CD56 mobility.